2000
DOI: 10.30843/nzpp.2000.53.3667
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent growth promotion of cabbage and lettuce from <i>Trichoderma</i> isolates

Abstract: Trichoderma isolates were evaluated for growth promotion effects on cabbage seedlings (Brassica oleracea L.) in glasshouse trials. Dipping transplants in spore suspensions (10 7 conidia/ml) of T. longipile (6Sr4 and 3Sr4-2) and T. tomentosum (5Sr2-2) increased (P<0.05) leaf area (58-71%), shoot dry weight (91-102%) and root dry weight (100-158%) compared with the untreated control in one trial but not in a second. In a field trial, yield of lettuce (Lactuca sativa L.) treated with T. longipile 6Sr4 was also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 9 publications
4
16
0
2
Order By: Relevance
“…It was noticed that Tricho-compost and Tricho-leachate although in small amount reduced mortality and allowed strawberry plant to grow vigorously. The results are in the line with the findings of Celar and Valic (2005) and Rabeerdran et al (2000) who reported that Trichoderma species promoted seedling establishment and enhancement of plant growth in vegetable crops. Nahar et.…”
Section: Mortality Percent Of Plants In the Maintenance Nursery And Ssupporting
confidence: 92%
“…It was noticed that Tricho-compost and Tricho-leachate although in small amount reduced mortality and allowed strawberry plant to grow vigorously. The results are in the line with the findings of Celar and Valic (2005) and Rabeerdran et al (2000) who reported that Trichoderma species promoted seedling establishment and enhancement of plant growth in vegetable crops. Nahar et.…”
Section: Mortality Percent Of Plants In the Maintenance Nursery And Ssupporting
confidence: 92%
“…This biostimulant activity has been studied widely for different isolates of Trichoderma sp. Harman and Björkman, 1998;Harman et al, 2004;Ousley et al, 1994;Rabeendran et al, 2000). Several mechanisms by which Trichoderma stimulate plant development have been suggested such as the production of growth-promoting metabolites and an increase in the uptake of nutrients by the roots as a result of plant-Trichoderma interaction (Altomare et al, 1999;Windham et al, 1986;Yedidia et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Composts from agro-industrial waste are considered more advantageous than other kinds of organic wastes [9], because they present a lower risk for pathogens, heavy metals and pharmaceuticals [8]. Furthermore, the efficiency of CTs can be increased if they are supplemented with beneficial microorganisms like Trichoderma sp., which can promote seedling establishment and enhance plant growth and plant defense reactions in some vegetable crops [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%